2017
DOI: 10.1111/ijd.13777
|View full text |Cite
|
Sign up to set email alerts
|

The association of smoking with contact dermatitis and hand eczema – a review

Abstract: Given the high prevalence of allergic contact dermatitis (ACD), irritant contact dermatitis (ICD), hand eczema (HE), and smoking, and the impact that smoking has on skin disease, the authors reviewed the existing literature to assess the association between smoking and contact dermatitis or hand eczema. Using the PubMed and SCOPUS databases, a literature search identified articles related to allergic contact dermatitis, irritant contact dermatitis, and hand eczema and a possible association with smoking. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…It therefore remains difficult to interpret causal relationships for lifestyle factors associated with the lifetime prevalence of hand eczema. Previous studies 27,28 also reported that exposed to cigarette smoking is a risk factor for hand eczema, but neither this study nor the Danish TOACS cohort 15 could confirm that relationship, and this inconsistency may differentiate between active and passive smoking. Passive smoking was the main exposure in this cohort.…”
Section: Discussioncontrasting
confidence: 80%
“…It therefore remains difficult to interpret causal relationships for lifestyle factors associated with the lifetime prevalence of hand eczema. Previous studies 27,28 also reported that exposed to cigarette smoking is a risk factor for hand eczema, but neither this study nor the Danish TOACS cohort 15 could confirm that relationship, and this inconsistency may differentiate between active and passive smoking. Passive smoking was the main exposure in this cohort.…”
Section: Discussioncontrasting
confidence: 80%
“…Also important are antimicrobial peptides and alarmins, skin tight junctions, natural moisturizing factors, immunoproteomes, proteases, lipids, smoking, etc. ( 24 , 25 ).…”
Section: The Pathomechanisms Of Contact Dermatitismentioning
confidence: 99%
“…Smoking increases the risk of contact dermatitis [ 94 , 95 ] and hand eczema [ 96 , 97 ]. The mechanism is still controversial in part [ 98 ]; however, cigarettes enhance the Th1 immune response and IFN-γ cytokine production [ 99 , 100 , 101 ], whereas nicotine itself seems to suppress the immune reaction, including dendritic cell maturation and T cell activation and migration [ 102 ].…”
Section: Daily Lifestyle and Inflammatory Skin Diseasesmentioning
confidence: 99%